Praktik Campur Kode Arab–Indonesia sebagai Konstruksi Identitas Santri dalam Kanal Youtube Jeda Nulis - Kholil, Mohammad Farhan; Maulana, Achmad Syafri; Pribadi, Mohammad (Aphorisme: Journal of Arabic Language, Literature, and Education, 2026)
This study analyzes Arabic-Indonesian code-mixing as a linguistic resource in the construction of santri (Islamic boarding school student) identity within the YouTube videos by Jeda Nulis and HAQIQI titled "HABIB JAFAR DIAJAK DZAWIN KE LAOS BUAT BELI LAOS" (Habib Jafar Taken by Dzawin to Laos to Buy Galangal??!!). The data consists of 13 selected utterances containing Arabic elements within Indonesian sentence structures comprising seven utterances by Habib Ja’far and six by Dzawin Nur obtained through thorough listening and verbatim transcription of the 1:07:04-long video. A qualitative descriptive approach was employed. The forms of code-mixing were classified according to Muysken’s typology, while their social functions were interpreted using Gumperz’s concept of "contextualization cues" and the principle of identity indexicality. The findings reveal ten instances of insertion, two of alternation, and one of congruent lexicalization. In Habib Ja’far’s speech, Arabic terms primarily function as epistemic devices that index scholarly authority and shape an "academic santri" identity orientation. In Dzawin’s speech, Arabic serves predominantly to activate *pesantren* memories, in-group humor, and solidarity, thereby shaping a "cultural santri" identity orientation. These findings confirm that similar structural forms do not necessarily yield identical social functions. Code-mixing operates contextually as a performative practice that negotiates the plurality of santri identities within digital communication spaces.